2004
DOI: 10.1097/01.gme.0000109314.11228.e5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of genistein on hot flushes in early postmenopausal women: a randomized, double-blind EPT- and placebo-controlled study.

Abstract: The present study confirms that genistein might have positive effects on hot flushes without a negative impact on endometrial thickness and suggests a future role of this phytoestrogen as a strategically therapeutic alternative in the management of postmenopausal symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
67
0
9

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(80 citation statements)
references
References 32 publications
4
67
0
9
Order By: Relevance
“…From the remaining human intervention studies provided, either separately in the consolidated list or in the systematic reviews, seven investigated the effect of soy isoflavones on both frequency and severity of hot flushes (Albertazzi et al, 2005;D'Anna et al, 2007;Khaodhiar et al, 2008;Knight et al, 2001;Nahas et al, 2007;St Germain et al, 2001;Upmalis et al, 2000), two investigated frequency only (Crisafulli et al, 2004;Faure et al, 2002) and three severity only (Cheng et al, 2007;Han et al, 2002;Kotsopoulos et al, 2000). Three of these studies also investigated the effect of soy isoflavones on night sweats (Cheng et al, 2007;St Germain et al, 2001;Upmalis et al, 2000).…”
Section: 3mentioning
confidence: 99%
See 2 more Smart Citations
“…From the remaining human intervention studies provided, either separately in the consolidated list or in the systematic reviews, seven investigated the effect of soy isoflavones on both frequency and severity of hot flushes (Albertazzi et al, 2005;D'Anna et al, 2007;Khaodhiar et al, 2008;Knight et al, 2001;Nahas et al, 2007;St Germain et al, 2001;Upmalis et al, 2000), two investigated frequency only (Crisafulli et al, 2004;Faure et al, 2002) and three severity only (Cheng et al, 2007;Han et al, 2002;Kotsopoulos et al, 2000). Three of these studies also investigated the effect of soy isoflavones on night sweats (Cheng et al, 2007;St Germain et al, 2001;Upmalis et al, 2000).…”
Section: 3mentioning
confidence: 99%
“…Trials were included if they measured frequency or severity of hot flushes. Six (Crisafulli et al, 2004;Faure et al, 2002;Penotti et al, 2003;Quella et al, 2000;Scambia et al, 2000;Upmalis et al, 2000) out of the 11 trials provided data for a meta-analysis. The Panel notes that this meta-analysis included a study in patients with breast cancer on tamoxifen medication (Quella et al, 2000), as well as a trial considered by the authors as being of poor quality (Scambia et al, 2000).…”
Section: 3mentioning
confidence: 99%
See 1 more Smart Citation
“…Abnormalities in reproductive health due to a high intake of phytoestrogens have been reported in several women [2,3]. Interestingly, genistein-a type of phytoestrogen-is known to have estrogenic properties, and various hormonal effects of this compound have been reported in women [4][5][6][7][8]. In toxicity studies, endocrine-mediated effects have been reported in rat pups of dams treated with genistein during the gestational and/or lactational periods [9][10][11][12][13], but these studies used soy-free or low-phytoestrogen diets.…”
mentioning
confidence: 99%
“…These results, known as the "Japanese Paradox" (data collected with Japonese population), induced Western people to consume soy and soy derivatives rich in isoflavones as genistein, daidzein, glycitein and the respective glucosidic forms (genistin, daidzin and glycitin). A large number of studies have attempted to demonstrate that soy consumption decreases the risk of developing several chronic diseases, in particular, cancer, osteoporosis [4,5], cardiovascular diseases [6], and also the relief of climacteric symptoms [7]. Up until now however, the majority of these benefits have not been proven [for review see 9].…”
Section: Introductionmentioning
confidence: 99%